(untitled) (Legal journal - Research in Legal and Social Sciences, 2024)
The article addresses the figure of autonomous confiscation, which is required when there is no criminal proceeding or conviction against the person who committed a punishable act, mostly related to organized crime, drug trafficking, money laundering, arms trafficking, human trafficking and others. The main objective of the research focuses on the analysis of landmark cases registered in the country, with a qualitative approach, non-experimental design, documentary type and descriptive scope, which begins with a previous approach to confiscation in general. This figure was already regulated in the Paraguayan Penal Code Law n.° 1160/1997, which devotes several articles to the matter, in Title V “Confiscation and Deprivation of Benefits”. However, the application of autonomous confiscation gained notoriety in the Paraguayan justice system once Law n.° 6431/2019 was passed, which creates the special procedure and, to this was added Law n.° 5876/2017 of SENABICO (National Secretariat for the Administration of Seized and Confiscated Assets). It is concluded that the current regulations and their application could generate violations of a constitutional, procedural and criminal nature in which, on the contrary, the State itself confiscates assets without considering the constitutional, procedural and criminal guarantees, rights and principles in the face of a poor investigation.